2020
DOI: 10.1149/1945-7111/abbb44
|View full text |Cite
|
Sign up to set email alerts
|

EIS Characteristics of Galvanic Couple of Aluminum Alloy and High-strength Steel under Thin Solution Films

Abstract: Galvanic corrosion of 6061-T6 (AA) coupled with high-strength steel (HSS) under 2 M NaCl solution films was investigated by electrochemical impedance spectroscopy (EIS). The AA is passivated in a 2 M NaCl solution and suffered pitting corrosion by galvanic coupling with HSS of the same surface area. Impedance of the AA/HSS couple was successfully measured under thin solution films (25-100 μm) using a potentiostat as a zero-resistance ammeter. The obtained impedance data shows a typical transmission line behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This arrangement equates to an average increase in I C /W of a factor of 8.2 for 25 μm in comparison to bulk solutions and would be comparable to 2 M NaCl. Tran et al reported a corrosion rate increase of a factor of 8 for a WL of 25 μm in comparison to bulk solutions in 2 M NaCl 59 which fits quite well with the modeled currents in Figs. 9a and 9b and shows the efficacy of this study and modeling techniques.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This arrangement equates to an average increase in I C /W of a factor of 8.2 for 25 μm in comparison to bulk solutions and would be comparable to 2 M NaCl. Tran et al reported a corrosion rate increase of a factor of 8 for a WL of 25 μm in comparison to bulk solutions in 2 M NaCl 59 which fits quite well with the modeled currents in Figs. 9a and 9b and shows the efficacy of this study and modeling techniques.…”
Section: Discussionsupporting
confidence: 77%
“…Various WL thicknesses were placed on top of the couple and with decreasing WL thickness, an increase in the coupling current density was measured for the AA/HSS couple. 59 This scenario is most similar to the cathode size of 0.01 m presented in Figs. 9a and 9b for 1 and 3 M NaCl.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar observations were reported by Van Nam Tran et al in 2020 using 6061-T6 aluminum alloy and high-strength steel. 62 As was noted in this paper, the impedance of the galvanic couple was between the impedances of the metals corroding separately (see Supplementary Material). However, aluminum seemed to be more active in their situation.…”
mentioning
confidence: 92%
“…The benefits of Al alloys include lower cost, better moldability, and higher specific strength than other lightweight materials such as Mg alloys and carbon fiber-reinforced plastics (CFRPs). [2][3][4] However, several technical challenges must be overcome in the fields of welding engineering, 5,6 refining and recycling, 7,8 and corrosion engineering [9][10][11][12][13][14] to hasten the widespread adoption of steel/Al alloy-based multimaterial structures. From a corrosion engineering point of view, the large difference between Al and Fe electrode potentials presents a challenge in designing Al alloys that are not susceptible to galvanic corrosion when coupled to steels.…”
mentioning
confidence: 99%